Photon-number resolving capability in SiPMs with electric field variation for radiation detection applications. (February 2019) - Lim, Kyung Taek; Kim, Hyoungtaek; Kim, Myungsoo; Kim, Yewon; Lee, Chang-yeop; Cho, Gyuseong
Abstract: In this paper, we investigate how the SiPM characteristics might vary in different electric field conditions in terms of parameters such as dark count rate and photon detection efficiency and present their relationships via SiPM photon–number–resolution (RSiPM ). The device samples were fabricated on 200 mm epitaxial wafers with a sensor area of 2.95 × 2.95 mm 2 and a micro-cell size of 65 µm. Keeping all other fabrication conditions identical, four different p-well implantation conditions were selected to produce four different electric field profiles: 5.0 × 10 12, 4.0 × 10 12, 3.0 × 10 12, and 2.5 × 10 12 atoms/cm 2 . From the fabricated samples, measurements on the breakdown voltage, dark count rate, and photon detection efficiency were obtained accordingly. Based on the measured device parameters, RSiPM of each sample was calculated to demonstrate how the electric field in the depletion region could influence the device performance. The intention of this study is to provide a guideline for obtaining the optimal SiPM parameters for target applications under a given fabrication condition. Highlights: The degree to which electric field could influence SiPM behavior is examined. SiPM photon–number–resolution as a design indicator for a target application. Reduced electric field as a reasonable approach for low photon flux detection.